Resistance to whitefly mediated by the Mi gene, acylsugars, and zingiberene in tomato - Oliveira, Celso Mattes de; Maluf, Wilson Roberto; Andrade, Thiago Matos; Menino, Gisele Cristina de Oliveira; Azevedo, Alcinei Místico (Comunicata Scientiae, 2023)
This study aimed to quantify and compare the effects of Mi gene, high leaf levels of acylsugars (AA), and zingiberene (ZGB) individually and in combination, regarding resistance of tomato lines to Bemisia argentifolii. The experiment included 21 genotypes selected simultaneously for high AA and ZGB content, cloned through rooting of axillary shoots with homogeneous sizes, and seven control lines produced from seeds, including 2 genotypes rich in AA (TOM-687 and TOM-688), two genotypes rich in ZGB (TOM-703 and TOM-704), and three lines with low levels of allelochemicals (cv. Santa Clara, TOM-584, and TOM-684), where the TOM-684 line carried the Mi gene. The experiment was conducted in a greenhouse using a randomized complete block design, comprising 28 treatments with 4 replications and 1 plant per plot. The AA and ZGB-rich lines showed higher resistance compared to the other control lines with low levels of allelochemicals, but the TOM-684 control line carrying the Mi gene was more resistant than the non-carriers ('Santa Clara' and TOM-584). The level of resistance conferred by ZGB was similar to that presented by AA. Both ZGB and AA provided higher levels of resistance compared to the Mi gene. The clones selected for both ZGB and AA simultaneously exhibited lower numbers of eggs and nymphs compared to the susceptible controls and were more resistant than the TOM-684 treatment. Overall, the clones even outperformed the lines rich in only one of the allelochemicals, demonstrating a synergistic effect between AA and ZGB for resistance when combined in the same tomato line.